IDENTIFICATION OF FLAVONOIDS IN IRAQI HONEY AND COMPARISON WITH OTHERS KIND BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY WITH UV DETECTION - Dhahir, Saadiyah A.; Hamed, Ameera H. (International Journal of Research -GRANTHAALAYAH, 2017)
Honey is rich in phenolic acids and flavonoids, which exhibit a wide range of biological effects and act as natural antioxidants. The analysis of polyphenols has been regarded as a very promising way of studying floral and geographical origins of honeys. The aim of this study was to determine, flavonoid in honey samples collected from different region in Iraq and Comparison with others kind. The flavonoids which measured in honey samples are (Myricetin, Quercetin, Hesperdin, Naringenin, Apigenin, Kaempferol, Chrisin). Chromatographic Separation was performed using a reversed phase column C18 and acetonitrile 60% (v/v) flow rate 1.0 ml/min, pH 5.5 at 280 nm. All calibration curves of the flavonoid compounds showed good linearity (r -0.9999) within the test range. Concentration of flavonoids ranged from Myricetin (1.903- 18.5) mg/kg, Quercetin (3.31-22.01) mg/kg, Hesperdin (4.55-16.2) mg/kg, Naringenin (3.2-24.68) mg/kg, Apigenin (6.76-28.81) mg/kg, Kaempferol (3.31-38.13) mg/kg, Chrisin (2.0-28.0) mg/kg respectively.